Tackling the computer overuse as a cause of chronic musculoskeletal disorders with the concept of a tangible personal persuasive avatar - Kosiński, Tomasz; Grzelak, Piotr; Kucharski, Przemysław; Romanowski, Andrzej; Chaniecki, Zbigniew (Wydawnictwo Politechniki Łódzkiej, 2015)
[...] The presented work, introducing a prototype of interactive avatars persuasive system into employees' natural workplaces, provided an opportunity of insight into human behavior at work and the possible problems to the company's productivity. The results of evaluation stage confirmed the impact that such a real avatar has on the user and revealed system improvement areas. It is intended to adjust robot's operations and sound persuasion stage. The evaluation phase is to be reviewed within the interdisciplinary team in order to provide the most accurate assessment methods. It was proven that human behavior can be changed in an unobtrusive way, without the need of announcing the official regulations, effectively.[...]
Keywords: interaktywny awatar - prototyp; wydajność firmy- badania; zachowania ludzi w pracy - badania; interaktywny awatar - wpływ na prace - badania; zmiana ludzkiego zachowania - sposoby; company performance - research; behavior of people at work - research; interactive avatar - influence on works - research; changing human behavior - ways; interactive avatar - prototype